2010
DOI: 10.2119/molmed.2010.00078
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA Desaturase-1 Is Associated with Insulin Resistance in Morbidly Obese Subjects

Abstract: Animal studies have revealed the association between stearoyl-CoA desaturase 1 (SCD1) and obesity and insulin resistance. However, only a few studies have been undertaken in humans. We studied SCD1 in visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) from morbidly obese patients and their association with insulin resistance, sterol regulatory element binding protein-1 (SREBP-1) and ATPase p97, proteins involved in SCD1 synthesis and degradation. The insulin resistance was calculated in 40 mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 47 publications
(75 reference statements)
4
31
1
Order By: Relevance
“…A recent study has shown that the treatment with palmitate for 48 h affects genome-wide mRNA expression and DNA methylation patterns in human pancreatic islets31. As in a previous study of our group performed in adipose tissue, we have also found a negative association between mRNA expression in PBMC and FFA levels4. However, we have not found significant association between SCD mRNA expression and SCD methylation levels.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…A recent study has shown that the treatment with palmitate for 48 h affects genome-wide mRNA expression and DNA methylation patterns in human pancreatic islets31. As in a previous study of our group performed in adipose tissue, we have also found a negative association between mRNA expression in PBMC and FFA levels4. However, we have not found significant association between SCD mRNA expression and SCD methylation levels.…”
Section: Discussionsupporting
confidence: 59%
“…As in our previous study, serum SCD activity indices were not associated with SCD mRNA expression in PBMC, neither with SCD methylation levels4. This could be explained because this measurement of SCD activity in serum mainly reflect the hepatic activity of SCD, since these indices are derived from fatty acids present in VLDL, LDL and HDL, which have their origin mainly in the liver, not in PBMC33…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Moreover, it remains possible that Scd1 mRNA expression was up-regulated in adipose tissue (Mangravite et al, 2007), peripheral blood cells (Vik-Mo et al, 2008), and/or skeletal muscle (Hulver et al, 2005). Alternatively, atypical antipsychotic medications may up-regulate Scd1 protein expression and/or enzymatic activity independent of effects on Scd1 transcription, and elevations in SCD1 protein expression in the absence of corresponding elevations in SCD1 mRNA expression have been observed previously (Garcia-Serrano et al, 2010). …”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, deleting Scd1 expression has been shown to decrease ceramide synthesis by down-regulating SPT expression in mice skeletal muscle (Peter et al, 2009). Furthermore, Scd1 deficiency increased insulin sensitivity in mice, whereas increased SCD activity contributed to the insulin resistance in humans and animals (Dobrzyn et al, 2010; Garcia-Serrano et al, 2011; Gutierrez-Juarez et al, 2006; Peter et al, 2009; Rahman et al, 2003). Thus, it is possible that SCD could play an important role in mediating the effects of fenretinide on apoptosis and insulin signaling.…”
Section: Introductionmentioning
confidence: 99%